'The classroom is a place where I'm alive:' one teacher's reflection on learning and life in the classroom. Issue 2 (3rd March 2016) - Steeg, Susanna M.
Abstract: This qualitative case study of one teacher's learning life describes how affective considerations influenced her learning and teaching. Classroom observations, interviews, and inquiry conversations informed the learning considerations that infused her first-grade classroom. The resulting descriptive vignettes showcase the various ways this experienced teacher trusted the significance of affect for her teaching and learning life together with children. This allowed her to co-construct a 'life curriculum' alongside students, demonstrating sensitivity to her students' academic, social, and emotional needs.